Leadless cardiac pacemakers: present and the future. (January 2018) - Chew, Derek S.; Kuriachan, Vikas
Abstract : Purpose of review: Pacing technology for many decades has been composed of a generator attached to leads that are usually transvenous. Recently, leadless pacemakers have been studied in clinical settings and now available for use in many countries. This includes the single-component Nanostim Leadless Cardiac Pacemaker and Micra Transcatheter Pacing System, as well as the multicomponent Wireless Stimulation Endocardial system. Recent findings: Clinical studies in single-component leadless pacing technology has shown that they can be successfully implanted with minimal complications. The follow-up studies also seem to confirm the findings from the initial clinical trials. These systems offer some advantages over a traditional pacing system comprised of a subcutaneous generator and transvenous leads. Summary: In many ways, these leadless systems are disruptive technologies that are changing the traditional pacemaker concept and preferred for some patients. Ongoing research is needed to better assess their long-term function, safety, and end-of-life strategies. In the future, multichamber leadless pacing is expected to be developed and perhaps obviating the need for transvenous leads and their associated complications.